Network meta-analysis of mineralocorticoid receptor antagonists for diabetic kidney disease - Wu, Yichuan; Lin, Huanjia; Tao, Yuan; Xu, Ying; Chen, Jiaqi; Jia, Yijie; Zheng, Zongji (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is one of the major causes of end-stage renal disease (ESRD). To evaluate the efficacy and safety of mineralocorticoid receptor antagonists (MRAs) in diabetic kidney disease patients, we conducted this network meta-analysis by performing a systematic search on PubMed, MEDLINE, EMBASE, Web of Science, the Cochrane Library, and Clinicaltrials.gov. A total of 12 randomized clinical trials with 15,492 patients applying MRAs covering spironolactone, eplerenone, finerenone, esaxerenone, and apararenone were included. The efficacy outcomes were the ratio of urine albumin creatine ratio (UACR) at posttreatment vs. at baseline, change in posttreatment estimated glomerular filtration (eGFR) vs. at baseline, and change in posttreatment systolic blood pressure (SBP) vs. at baseline. The safety outcome was the number of patients suffering from hyperkalemia. High-dose finerenone (MD -0.31, 95% CI: -0.52, -0.11), esaxerenone (MD -0.54, 95% CI: -0.72, -0.30), and apararenone (MD -0.63, 95% CI: -0.90, -0.35) were associated with a superior reduction in proteinuria in patients with DKD. Regarding the change in eGFR, the results of all drugs were similar, and finerenone may have potential superiority in protecting the kidney. Compared with placebo, none of the treatments was associated with a higher probability of controlling systolic blood pressure during treatment. Moreover, 20 mg of finerenone, esaxerenone, and spironolactone presented a higher risk of hyperkalemia. This Bayesian network meta-analysis was the first to explore the optimal alternative among MRAs in the treatment of DKD, and revealed the superiority of 20 mg finerenone among MRAs in treating DKD.